The Nutritive value and in-vitro digestibility of peels and pomaces of different citrus species: Nutritive value assessment for citrus species by products - Olowu, OO; Yaman Firincioglu, S (Journal of the Hellenic Veterinary Medical Society, 2023)
The nutritive value and invitro digestibility of agro-industrial byproducts of Citrus aurantium, Citrus paradisi, Citrus reticulata, Citrus limon and Citrus sinensis were assessed for their feed modification potential. Nutritive value assessment was done through chemical analysis while the ANKOM Daisy II incubator method was used to determine the invitro digestibility. At p>0.05, there was no statistical significance for nutritive value of the citrus byproducts for the five species. The agro-industrial by-products had significantly different phenolic content. Invitro digestibility of the peels significantly differed from the pomaces (p<0.001). The byproducts of the five citrus species showed potential to be considered as non-forage energy sources in ruminant feed. Lemon byproducts had high protein but not sufficient as a single protein source while bitter orange pomace may be considered for antioxidant capacity and high digestibility. Abundance of citrus agro-industrial byproducts, nutritive value potentials and their digestibility makes it a good strategy for ruminant feed modification and utilization.